Shooting habits and habitats- effects of education and legislation on the phasing out of lead shot. Issue 118 (April 2021) - Widemo, Fredrik
Graphical abstract: Highlights: Compliance with the bans on lead shot by Swedish shooters was low. Voluntary phasing out of lead shot was rare. Education and communication increased compliance and voluntary phasing-out. Restrictions should be based on proportionate, unambiguous legislation. Current efforts in legislation, enforcement and education are insufficient. Abstract: Achieving sustainability often requires fostering changes in norms and behaviours through a combination of restrictions and aware-raising activities. The phasing out of lead in ammunition to reduce lead poisoning in waterfowl provides a case in point. Twenty years after the Parties to the African Eurasian Waterbird Agreement (AEWA) committed to phase out lead shot in wetlands, such bans have been implemented in a third of Europe only. Furthermore, while evidence is scant, compliance varies widely where bans have been introduced. As a result, waterfowl are still suffering from lead poisoning. Here, I survey the use of different types of shot while practicing and when taking game in different habitats in Sweden, one of the Parties to AEWA. Furthermore, I test the hypotheses that mandatory shooter education, or stakeholder communication, influence compliance with existing restrictions in Sweden, as well as the voluntary phasing out of lead shot where its use still is permitted. More than half of the shooters practiced using lead and a third used lead shot over what they considered as wetlands, in both cases in violation of the current legislation. Furthermore, what constitutes a wetland appears to have been unclear to many shooters, especially in alpine areas. Both mandatory education and stakeholder communication were positively related to compliance. Only 12–15 % used lead free alternatives in shooting over habitats where the use of lead shot is permitted. There was a weak positive relationship between stakeholder communication and the voluntary phasing out of lead shot, but no effect from education. I suggest that the planned and ongoing phasing out of lead in ammunition should rest on a combination of legislation, enforcement, education and stakeholder communication in order to be successful. The findings add to our general understanding of how to turn environmental policy into sustainable management actions in practice.